Improved outcomes after radiotherapy for prostate cancer: Anticoagulation, antiplatelet therapy, and platelet count as key factors in disease progression - Stanley I. Gutiontov; Kevin S. Choe; Jonathan L. Miller; Stanley L. Liauw (Cancer Medicine)
Abstract Background Several studies have suggested that antiplatelet (AP) or anticoagulant (AC) therapy may improve outcome in men with prostate cancer. We evaluated the effects of AP/AC therapy and tested the hypothesis that platelet count may also be associated with outcomes. Methods A total of 482 patients received primary radiotherapy (median dose 72 Gy) for nonmetastatic prostate cancer; 49% received androgen deprivation therapy. NCCN risk was low/intermediate/high risk in 39%/39%/22%. AP/AC therapy and platelet counts were analyzed with respect to freedom from biochemical failure (FFBF, nadir+2), distant metastasis (FFDM), and cause specific survival (CSS). Results After a median follow‐up of 103 months, 10‐year FFBF, FFDM, and CSS were 77%, 92%, and 96%, respectively. The 10‐year cumulative incidence of BF and DM (with death as a competing event) was 19% and 7.0%, respectively. The 32% of men on AP/AC therapy had a lower incidence of 10‐year BF (P = .016) and a trend toward a lower incidence of DM (P = .084) and CSS (P = .091). In the entire cohort, lowest platelet quartile (platelet count <187) was associated with higher 10‐year BF (31% vs 16%, P = .0042) but not DM (9.4% vs 5.2%, P = .22) nor CSS (P = .76) compared with those patients with platelet count ≥187. AP/AC therapy was associated with a larger absolute reduction in BF for men with lowest platelet quartile (10‐year BF of 21% vs 38%, P = .092) vs platelet ≥187 (10‐year BF of 10% vs 18%, P = .053). Lowest platelet quartile remained associated with higher BF and DM on multivariable analysis controlling for risk category, WBC, and Hg. Conclusion AP/AC was associated with improved FFBF. Low platelet count was associated with inferior FFBF and FFDM after prostate radiotherapy. This association was tempered when antiplatelet and anticoagulant therapy was administered.